Interhospital and interindividual variability in secondary prevention: a comparison of outpatients with a history of chronic coronary syndrome versus outpatients with a history of acute coronary syndrome (the iASPIRE Study). Issue 1 (25th June 2021) - Curneen, James MG; Judge, Conor; Traynor, Bryan; Buckley, Anthony; Saiva, Lavanya; Murphy, Laura; Murray, Donal; Fleming, Sean; Kearney, Peter; Murphy, Ross T; Aleong, Godfrey; Kiernan, Thomas J; et al.
Abstract : Background: Studying variability in the care provided to secondary prevention coronary heart disease (CHD) outpatients can identify interventions to improve their outcomes. Methods: We studied outpatients who had an index CHD event in the preceding 6–24 months. Eligible CHD events included acute coronary syndrome (ACS) and coronary revascularisation for stable chronic coronary syndrome (CCS). Site training was provided by a core team and data were collected using standardised methods. Results: Between 2017 and 2019, we enrolled 721 outpatients at nine Irish study sites; 81% were men and mean age was 63.9 (SD ±8.9) years. The study examination occurred a median of 1.16 years after the index CHD event, which was ACS in 399 participants (55%) and stable-CCS in 322. On examination, 42.5% had blood pressure (BP) >140/90 mm Hg, 63.7% had low-density lipoprotein cholesterol (LDL-C) >1.8 mmol/L and 44.1% of known diabetics had an HbA1c >7%. There was marked variability in risk factor control, both by study site and, in particular, by index presentation type. For example, 82% of outpatients with prior-ACS had attended cardiac rehabilitation versus 59% outpatients with prior-CCS (p<0.001) and there were also large differences in control of traditional risk factors like LDL-C (p=0.002) and systolic BP (p<0.001) among outpatients with prior-ACS versus prior-CCS as the index presentation. Conclusions: Despite international secondary prevention guidelines broadly recommending the same risk factor targets for all adults with CHD, we found marked differences in outpatient risk factor control and management on the basis of hospital location and index CHD presentation type (acute vs chronic). These findings highlight the need to reduce hospital-level and patient-level variability in preventive care to improve outcomes; a lesson that should inform CHD prevention programmes in Ireland and around the world.